Generation of positively and negatively charged molecular ions during sputtering of a copper target by low-energy Ar+ ion bombardment in a dilute argon/oxygen gas mixture. (12th March 2019) - Hippler, Rainer; Denker, Christian
Abstract: Generation of positively and negatively charged ions during 500 eV Ar + ion bombardment of a copper surface in a dilute argon/oxygen atmosphere was investigated by means of energy-resolved mass spectrometry. Ar +, Ar 2+, Ar2 +, O 2 +, and O 2 − ions are produced by gas phase reactions. Cu n +, Cu n − ( n = 1−3), ArCu +, O +, and O − ions are produced by interaction with the oxygen-covered Cu surface. Interaction with reactive oxygen species gives rise to the formation of positively or negatively charged copper oxide ions.